On improvement of computational efficiency in FEM calculations of incompressible fluid flow and heat transfer - Banaszek, Jerzy (Computer Assisted Methods in Engineering and Science; Vol 2 No 2 (1995), 2023)
The operator splitting algorithm has been applied in FEM analysis of fluid flow and heat transfer to improve the computational efficiency through the use of the optimum FEM models and the optimum solvers independently for convection and diffusion. The need for decoupling convection and diffusion operators in FEM calculations comes from the behavioural error analysis, where conditions have been studied for a proper representation of major physical features of the convective-diffusive transport phenomenon on a coarse grid. The accuracy and efficiency of the algorithm have been verified by solving two pertinent benchmark problems of recirculating flow and free convection. The results obtained show that solutions of both equal- and unequal-order FEM interpolations are free from wiggles and spurious pressure modes and they fit fairly well the results reported elsewhere.